Hydromineral potential of São Paulo state aquifers - Garpelli, Lia Nogueira [UNESP]; Gastmans, Didier [UNESP] (Universidade Federal do Rio Grande do Sul, 2020)
The state of São Paulo leads the Brazilian production of bottled mineral water. Due to its complex hydrogeological framework, there is a variety of sedimentary and fractured aquifers, which can contribute to occurrences of waters with different hydromineral characteristics. Thus, the main objective was to evaluate the hydromineral potential of the São Paulo aquifers, according to the Mineral Water Code (CAM) and related international legislation, based on a public database of analytical reports from 276 underground water wells of Environmental Company of the State of São Paulo (CETESB). When analyzed on the concentrations of Total Dissolved Solids (TDS), it was observed that groundwater had a varying degree of mineralization, with the most mineralized waters associated with Serra Geral (SASG), Tubarão (SAT) and Bauru (SAB) aquifer systems. However, only 8.7% of the waters would be qualify as minimum to low levels of TDS, under United States legislation. Similarly, only two samples would be classified as very low mineralized and, 81.5% as low mineralized, by European legislation. By the classifications provided by CAM, the samples were characterized by temperature, predominantly, as cold and hypothermal, and a small portion as mesothermal and hypothermal. The colder waters prevailed in Cristalino aquifer (SAC), while the higher temperatures occurred in Guarani (SAG). All aquifers had hydromineral potential by chemical classification, due to fluoride concentration, followed in decreasing order, by lithium in SAC, vanadium in SASG, alkaline bicarbonate in SAT, sulfate and selenium as a mixed water in SAT and SASG.
Potencial hidromineral dos aquíferos do estado de São Paulo
Keywords: Brazilian Mineral Water Code; Groundwater; Hydrochemical; State of São Paulo